Management and clinical outcomes after lung transplantation in patients with pre‐transplant Mycobacterium abscessus infection: A single center experience. Issue 3 (16th April 2019) - Perez, Alyssa A.; Singer, Jonathan P.; Schwartz, Brian S.; Chin‐Hong, Peter; Shah, Rupal J.; Kleinhenz, Mary Ellen; Gao, Ying; Venado, Aida; Leard, Lorriana E.; Golden, Jeffrey A.; Kukreja, Jasleen; Greenland, John R.; et al.
Abstract: Background: Preoperative Mycobacterium abscessus infection is often considered a contraindication to lung transplantation because of its association with poor outcomes after transplant. Detailed strategies for bridging to transplant, post‐operative management, and data regarding outcomes are lacking. Methods: We reviewed outcomes in subjects with M abscessus infection who underwent lung transplantation between 2010 and 2018 at the University of California San Francisco. M abscessus infection was defined by American Thoracic Society (ATS) criteria. Data collected included age, FEV1, BMI, LAS, antibiotic regimens, and other management decisions. Time to chronic lung allograft dysfunction (CLAD) and survival were also assessed. Results: Of 387 lung transplant recipients, seven were infected with M abscessus at the time of listing. All received multiple antibiotics before transplant. While all subjects converted to smear negative for acid‐fast bacilli before listing, five of the seven remained culture‐positive at the time of transplant. After transplant, subjects received a median of 6 months of a multi‐antibiotic regimen. One subject developed a post‐operative M abscessus soft tissue infection that was treated medically. Six of the seven subjects survived the observation period; one died unrelated to M abscessus . Time to CLAD and survival were similar to a contemporary comparator group of CF transplant recipients. Conclusion: Lung transplant recipients with M abscessus infection have a low incidence of recurrent infection, excellent survival, and freedom from CLAD when an aggressive management and surveillance strategy is utilized. Given these findings, M abscessus infection may not be considered a contraindication to lung transplantation.